Impact of Running Exercise on Intervertebral Disc: A Systematic Review - Shu, Dingbo; Dai, Siyu; Wang, Jianping; Meng, Fanjing; Zhang, Chuan; Zhao, Zhenhua (Sports health, 2024)
Context: Running is one of the most popular sports worldwide. However, controversies exist regarding how running affects runner’s intervertebral discs (IVD). Objective: The purpose of this study was to systematically review studies that evaluated IVD morphology or composition changes in response to running exercise, to determine the impact of running exercise on IVD. Data Sources: A systematic literature search was performed for 4 major databases: PubMed, Cochrane, Embase, and Web of Science. Study Selection: Inclusion criteria were as follows: (1) healthy people without known IVD disease or major complications such as tuberculosis (IVD degeneration or low back pain are considered as minor complications); (2) subjects performed 1-time or regular running exercises; (3) pre and post comparison of runners or comparison between runners and healthy control subjects; (4) direct or indirect IVD morphology or composition measured; (5) IVD assessed before and after either acute or chronic running exercise, or compared cross-sectionally between runners and controls. Exclusion criteria were as follows: (1) reviews, editorials, letters or abstracts only; (2) animal studies; (3) subjects performed exercise other than running. Study Design: Systematic review. Level of Evidence: Level 3. Data Extraction: The extracted data included study design and primary outcomes of the included studies. The Newcastle-Ottawa scale (NOS) was used to evaluate study quality and risk of bias. Results: A total of 13 studies with 632 participants were included in the final analysis; 4 studies measured IVD changes using stature or spinal height, and the other 9 measured IVD changes using magnetic resonance imaging; 6 studies found that running acutely and negatively impacts IVD; 3 out of 5 cross-sectional studies found that IVD parameters are better for runners than controls; 1 longitudinal study found no significant difference in IVD before and after training for marathon in runners; 1 longitudinal study found no significant difference in changes of IVD between runners and controls after 15 years of follow-up. Conclusion: Negative changes in IVD exist for a short period of time after running, which may be due to the temporary compression pushing water content out of the disc. Cross-sectional studies suggest that long-term running exerts a mild positive effect on IVD; however, this inference has not been confirmed by high-quality longitudinal studies.